The role definition of corporate social responsibility in ensuring sustainable development of an enterprise - Nazarova, Galyna; Nazarov, Nikita; Semenchenko, Andrii; Semenchenko, Alina; Demchenko, Kateryna (Technology audit and production reserves, 2025)
The relevance of this paper is due to the close connection between corporate social responsibility and ensuring sustainable development of enterprises to achieve the long-term goals of the economy and society in the post-war recovery of Ukraine. The paper is aimed at studying corporate social responsibility of enterprises with a focus on customer commitment and developing a mechanism for implementing a system of corporate social responsibility of enterprises based on certain principles of sustainable development. The paper considers the main approaches to defining corporate social responsibility, its impact on society and business, as well as the prospects for development in the context of global challenges. The object of research is the processes of formation and implementation of corporate social responsibility at enterprises in the context of ensuring their sustainable development. The development of the concept of corporate social responsibility can be traced from an ethical approach that emphasizes the moral obligations of companies to a strategic approach that considers social responsibility as a tool for creating long-term value. It is emphasized that integration of corporate social responsibility into the business strategies of leading companies contributes to sustainable development, competitiveness and formation of a positive image. The results indicate that managers of enterprises should pay special attention to the implementation of the corporate social responsibility system during crises and military conflicts and coordinate its implementation with the principles of sustainable development. It is determined that social responsibility of business is a prerequisite for maintaining social cohesion, helping vulnerable groups of the population and strengthening national resilience. The study provides companies with the opportunity to develop their own mechanism for the formation of a corporate social responsibility system according to the proposed step-by-step algorithm. The practical application of the research results allows enterprises to determine specific strategies for implementing corporate social responsibility, adhering to the principles of environmental balance, economic sustainability and social justice.